2009
DOI: 10.1007/s11284-009-0643-0
|View full text |Cite
|
Sign up to set email alerts
|

Variation in seed germination between populations of five sub‐alpine woody species from eastern Qinghai‐Tibet Plateau following dry storage at low temperatures

Abstract: Effects of cold-dry storage on dormancy break and viability were determined for seeds of the five subalpine woody species Philadelphus incanus, Berberis vernae, Berberis dubia, Betula utilis, and Picea purpurea collected along an altitudinal gradient on the eastern part of the Qinghai-Tibet Plateau in China. Germination tests were conducted at 20/5°C for seeds stored dry at ambient room temperature for 4 weeks and then at 3-4°C for 0, 6, 12, and 24 weeks. Dormancy break during dry storage, i.e., afterripening,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 12 publications
6
19
0
1
Order By: Relevance
“…2) suggest that the level of seed dormancy of R. multibracteata increases with increasing elevation at a small spatial scale. Our findings agree with most of other studies at broad regional scales in woody species (Pendleton and Meyer 2004;Wang et al 2010) and Correlations between dormancy and genetic variation have been found along a climatic gradient at regional (Wagmann et al 2012) and local scales (Ferna´ndez-Pascual et al 2013). Further study should focus on the effects of genotype, environments or their interaction on the level of seed dormancy of R. multibracteata along the elevational gradient.…”
Section: Variation Of the Level Of Dormancy Along The Elevational Grasupporting
confidence: 93%
See 2 more Smart Citations
“…2) suggest that the level of seed dormancy of R. multibracteata increases with increasing elevation at a small spatial scale. Our findings agree with most of other studies at broad regional scales in woody species (Pendleton and Meyer 2004;Wang et al 2010) and Correlations between dormancy and genetic variation have been found along a climatic gradient at regional (Wagmann et al 2012) and local scales (Ferna´ndez-Pascual et al 2013). Further study should focus on the effects of genotype, environments or their interaction on the level of seed dormancy of R. multibracteata along the elevational gradient.…”
Section: Variation Of the Level Of Dormancy Along The Elevational Grasupporting
confidence: 93%
“…Elevational gradients offer steep environmental gradients across short spatial scales, representing opportunities to conduct exciting biological experiments in a natural setting (Korner 2007). Most studies have shown dormancy tends to increase with increasing elevation (Meyer et al 1995;Cavieres and Arroyo 2000;Pendleton and Meyer 2004;Wang et al 2010) but exceptions to this pattern have also been found (Farhadi et al 2013). For example, in Phacelia secunda, initiation of germination required increasingly longer periods of stratification with elevation, and proportionately fewer seeds germinated for any one stratification treatment at the higher elevations (Cavieres and Arroyo 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such types of report are available on other species of Berberis i.e. B. vernae and B. dubia (Wang et al 2010). While analyzing the responses of dry cold storage on selected Berberis species, it was found that an appropriate storage period does affect the germination percentage.…”
Section: Effect Of Storagementioning
confidence: 99%
“…That is, a combination of dormant and nondormant species and, among dormant species, a similar proportion displaying PD and MPD. The dormancy classes described here were determined following long periods of storage at 15% relative humidity (initially at 15°C and subsequently at -18°C), which may have affected the depth of dormancy (Kaye, 1997;Andersson & Milberg, 1998;Baskin & Baskin, 1998;Wang et al, 2010). Baskin & Baskin (1998), noted that the relative humidity must be at least 30-40% for species to come out of dormancy during storage, and Hoyle et al (2008b) found that dry storage of seeds under the conditions used here (15°C and 15% relative humidity) had no effect on dormancy and subsequent germination of Goodenia fascicularis F.Muell.…”
Section: Dormancy Classificationmentioning
confidence: 99%